2009
DOI: 10.1111/j.1743-6109.2008.00981.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific Cerebral Activation Due to Visual Erotic Stimuli in Male-to-Female Transsexuals Compared with Male and Female Controls: An fMRI Study

Abstract: Introduction Transsexuals harbor the strong feeling of having been born to the wrong sex. There is a continuing controversial discussion of whether or not transsexualism has a biological representation. Differences between males and females in terms of functional imaging during erotic stimuli have been previously described, revealing gender-specific results. Aim Therefore, we postulated that male-to-female (MTF) transsexuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 33 publications
3
44
1
8
Order By: Relevance
“…The assumption that GD could be considered a DSD is based on the demonstration in maleto-female (MtF) and female-to-male (FtM) transsexuals of a sex reversal in terms of volume and cell number of sexdimorphic brain nuclei, such as the central portion of the bed nucleus of the striaterminalis (BNSTc) [38][39][40], the gray matter in the right putamen [41], and the interstitial nuclei 3 and 4 of the anterior hypothalamus (INHAH3 and INAH4) [42]. These findings have been further enhanced by the demonstration of gender-atypical brain activation patterns in processing steroid-based odors and erotic stimuli [43,44]. In addition, a recent study found that FtM GD individuals show stronger more female-typical otoacustic emissions compared to control boys, suggesting that boys with GD might have been exposed to relatively lower amounts of androgens during early development [45].…”
Section: Introductionmentioning
confidence: 79%
“…The assumption that GD could be considered a DSD is based on the demonstration in maleto-female (MtF) and female-to-male (FtM) transsexuals of a sex reversal in terms of volume and cell number of sexdimorphic brain nuclei, such as the central portion of the bed nucleus of the striaterminalis (BNSTc) [38][39][40], the gray matter in the right putamen [41], and the interstitial nuclei 3 and 4 of the anterior hypothalamus (INHAH3 and INAH4) [42]. These findings have been further enhanced by the demonstration of gender-atypical brain activation patterns in processing steroid-based odors and erotic stimuli [43,44]. In addition, a recent study found that FtM GD individuals show stronger more female-typical otoacustic emissions compared to control boys, suggesting that boys with GD might have been exposed to relatively lower amounts of androgens during early development [45].…”
Section: Introductionmentioning
confidence: 79%
“…While little is known about the etiopathogenesis of gender dysphoria (GD) (Medras & Jozkow, 2010), functional neuroscience revealed evidence for greater similarities of GD individuals with their aspired than with their assigned gender in tasks differentiating between men and women (Carrillo et al., 2010; Gizewski et al., 2009; Schoning et al., 2010; Ye et al., 2011). Because of its stimulus‐unrelated and task‐free methodology, rs‐fMRI provides an unbiased strategy to investigate neurobiological functioning in GD and allows direct comparison of participants with their assigned and aspired gender.…”
Section: Discussionmentioning
confidence: 99%
“…Female‐like structures in female‐to‐male GD individuals before hormonal treatment (FtMs) (Rametti et al., 2010) and structural changes through hormonal treatment (Rametti et al., 2012) have also been observed. Functional MRI (fMRI) studies provide a similarly complex pattern with activation similarities between GD individuals and their aspired gender (Carrillo et al., 2010; Gizewski et al., 2009; Schoning et al., 2010; Sommer et al., 2008; Ye et al., 2011) in several tasks sensitive to sex and/or gender differences in neural activity (Lykins, Meana, & Strauss, 2008; Semrud‐Clikeman, Fine, Bledsoe, & Zhu, 2012; Thomsen et al., 2000). However, the number and the reported sample sizes of fMRI studies investigating such differences is small, and therefore drawing definite conclusions about whether the brain activity of GD individuals is more similar to their aspired or their assigned gender is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms that are exhibited in the early stage include increased body hair attributed to the fact that there was an increase secretion of corticosteroids, which also causes excess fats deposits at the back and sometimes loss of hair. When there is excess secretion of androgenic steroids, the patient will exhibit an increase in libido and therefore, develop hypersexuality (29).…”
Section: Adrenocortical Carcinomamentioning
confidence: 99%